2019
DOI: 10.1097/nmd.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Medical Students

Abstract: Mental health illnesses are increasing in severity and number among medical students. This study aims to estimate the prevalence of mental disorders among medical students and their associated factors. Nine hundred students were selected from Mansoura Faculty of Medicine by the cluster sampling method. Data were collected using an Arabic self-administered questionnaire and the Arabic version of the Symptoms Checklist 90 Revised. Both bivariate and multivariate logistic regression analyses were done. Approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…On the other hand, OCD can adversely affect academic performance, general well-being, social interaction, and suicidal thoughts. Issues that might have a huge impact on life unless being diagnosed early and properly managed [ 4 , 6 , 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, OCD can adversely affect academic performance, general well-being, social interaction, and suicidal thoughts. Issues that might have a huge impact on life unless being diagnosed early and properly managed [ 4 , 6 , 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent online study [ 21 ], including N = 185 university students studying in Germany found that 36.6% of the university students (women and men) report experiencing depressive symptoms, 41.83% (women and men) reported experiencing high levels of state anxiety, and all students reported experiencing stress due to excessive demands and uncertainty in finances, job, or social relationships. These prevalence rates have actually been found in cohort studies including university students all over the globe, irrespective of culture before the outbreak of the pandemic [ 17 22 , 50 53 ]. In relation to these pre-pandemic prevalence rates, the prevalence of state anxiety and of depressive symptoms in the current sample seem to have more than doubled during the pandemic time period.…”
Section: Discussionmentioning
confidence: 69%
“…Regarding pandemic risk groups, previous cross-cultural pre-pandemic surveys have shown high prevalence rates of anxiety and depression among university students across countries [ 17 22 , 50 53 ]. Therefore, the WHO’s concerns about the psychological consequences of the COVID-19 pandemic on mental health and well-being might affect university students as a population group as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations